Significance of pH cyclization in amelogenesis - Róbert Rácz; Martin C. Steward; Pamela Denbesten; Gábor Varga; Beáta Kerémi (Fogorvosi Szemle, 2021)
The process of amelogenesis is well understood at the histomorphological level, but the regulation of crystal formation and the underlying molecular mechanisms are still largely unknown. Ameloblast cells derived from the oral epithelium regulate enamel maturation. In addition to the secretion of matrix proteins and the transport of minerals, pH regulation is also essential as the formation of hydroxyapatite crystals generates large quantities of H+ ions, which must be neutralized by the secretion of HCO3−. During the maturation phase, the phenomenon of pH cycling is of paramount importance, during which a rearrangement of tight-junctions can also be observed. Genetic or environmental impairment of transport and regulatory processes (e.g. dental fluorosis) leads to the development of enamel defects. To explore these processes, we have developed an in vitro model suitable for functional studies. Central elements of this model are that differentiated ameloblast-derived cells cultured on a permeable membrane express ameloblast-specific protein markers, form tight junctions, become functionally polarized, and are capable of vectorial HCO3− secretion. The results of our own experimental work contribute to a better understanding of the molecular mechanism of pH cycling of ameloblast cells.